ANALYSIS OF THE FACTORS INFLUENCING LONG STUDIES AND STUDENT ACHIEVEMENT INDEX EDUCATION OF MECHANICAL ENGINEERING OF PALANGKARAYA UNIVERSITY - Whendy Trissan (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2015)
This research was carried out to uncover and analyze factors that affect student achievement index gains. The population of the research was the student education courses mechanical engineering University of Palangkaraya. Sampling is done in a manner stratified cluster random sampling with a sample research amounted to 45 students. The results showed that the index of Student Achievement (GPA) is influenced by multiple variables such as: interest, methods of studying, IQ, mood, divide the time, relationships with family, the explanation lecturer, the atmosphere of the place of residence, in addition to lectures, environmental adaptation, the radar of parents, parents ' attention, the Association, the ability of socialization, financial condition, mood learning campus and the ability of capturing material, after an analysis of the factors and process of reduction obtained 6 factors affecting students GPA and Study Old, the Sixth factor is the factor of interest, method of learning, motivation factors, Factors of the elderly, Financial and environmental factors. The results of this research is beneficial to students and lecturers especially decisive policies in the Education of mechanical engineering University of Palangkaraya, to develop and improve the factors that affect Long studies and student GPArelated policy in the campus in order to provide a positive contribution for obtaining student GPA.